The Roles of CRM in the Telecommunication Industries in Singapore - CHONG, Yeng Keat (2007)
This study evaluated the CRM strategy of Singapore Telecommunications by assessing its technological infrastructure, technical proficiency, and its implementation based on its personnel. The result of the study revealed that Singapore Telecommunications have been effective in implementing its CRM strategy both in the personnel level and on how their subscribers perceive their CRM strategy. The respondents have provided a positive feedback on the CRM strategy of SingTel and how it is implemented in the rank and file level using technologies. The level of quality of products and brands of SingTel continues to meet the needs of the customers; the level of perception of the respondents also increases. Consequently, SingTel was able to effectively institute technologies in the company and provide the technical skills to its personnel and implement an efficient CRM strategy. In terms of effectiveness of CRM strategy of Singapore Telecommunications in building brand loyalty among Singaporeans, the company has been reorganised as well as functional lines rather than by service channel which greatly facilitates the implementation of the CRM strategy.